2005
DOI: 10.1128/iai.73.8.4955-4959.2005
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Neutrophil Migration Associated with Specific Bovine CXCR2 Genotypes

Abstract: Bovine mastitis continues to be the most detrimental factor for profitable dairying. Recent research conducted within our laboratory has identified a genetic marker in the CXCR2 gene associated with mastitis susceptibility. The objective of the present study was to evaluate the migratory ability of neutrophils from cows with different CXCR2 ؉777 genotypes. Neutrophils isolated from peripheral blood of 30 Holstein cows were tested for in vitro migration and adhesion molecule expression. Cows with the CC or GC g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 34 publications
3
34
3
Order By: Relevance
“…Therefore, CXCR1 may have a potential role in the recruitment of bovine neutrophils into the mammary gland when an infection occurs. The nonsynonymous substitution at the CXCR1 c.+777G>C SNP resulted in the replacement of glutamine with histidine at amino acid 245 within the third intercellular loop of the receptor region for G protein coupling activation, which is related to the functional characteristics of neutrophil migration, production of reactive oxygen species (Rambeaud and Pighetti, 2005), and release of intracellular calcium (Rambeaud and Pighetti, 2007). The c.337A>G SNP changed the 113th amino acid from isoleucine to valine, whereas the c.365C>T mutation changed alanine to valine at position 122 within the putative 3rd intercellular loop of the receptor region for G protein coupling activation of CXCR1 (360 amino acids).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, CXCR1 may have a potential role in the recruitment of bovine neutrophils into the mammary gland when an infection occurs. The nonsynonymous substitution at the CXCR1 c.+777G>C SNP resulted in the replacement of glutamine with histidine at amino acid 245 within the third intercellular loop of the receptor region for G protein coupling activation, which is related to the functional characteristics of neutrophil migration, production of reactive oxygen species (Rambeaud and Pighetti, 2005), and release of intracellular calcium (Rambeaud and Pighetti, 2007). The c.337A>G SNP changed the 113th amino acid from isoleucine to valine, whereas the c.365C>T mutation changed alanine to valine at position 122 within the putative 3rd intercellular loop of the receptor region for G protein coupling activation of CXCR1 (360 amino acids).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the previous association and functional studies for CXCR2 (GenBank accession No. NM_174360.2) performed by Youngerman et al (2004a) and by Rambeaud and Pighetti (2005) correspond to CXCR1. The high degree of polymorphism of CXCR1 was again verified.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of neutrophils to migrate into infected tissues is dependent upon the recognition of inflammatory mediators such as (ELR)CXC chemokines (which possess the sequence Glu-Leu-Arg preceding the first two Cys) and the complement fragment C5a through specialized receptors. Recently, it was shown that a single polymorphism nucleotide (SNP) within the CXCR2 gene (one of the two receptors for (ELR)CXC chemokines) was associated with impaired neutrophil migration and correlated with the frequency of subclinical mastitis in Holstein cows [150,209]. This correlation needs to be validated on a large scale and the individual allele effects on leucocyte migration needs to be measured experimentally, but this kind of finding is promising, since it may herald the advent of effective means of marker-assisted selection for mastitis resistance.…”
Section: Genetic Selectionmentioning
confidence: 99%
“…In particular, two SNPs, CXCR1+777 and CXCR1-1768, are noteworthy polymorphisms that showed associations with subclinical mastitis or milk quality in dairy cattle. Furthermore, SNP CXCR1+777 does have an effect on neutrophil functions [15][16][17]. We hypothesized that the association between the SNPs in the bovine CXCR1 gene and susceptibility to infectious disease would be present in Japanese Black cattle as well as dairy cattle.…”
Section: Discussionmentioning
confidence: 99%
“…A significant association has been detected between the SNP CXCR1+777 genotype and the percentage of subclinical mastitis cases in Holstein cows [22]. The SNP has also been demonstrated to be associated with the functional characteristics of neutrophil migration to recombinant human IL-8 [15], the ability to suppress apoptosis and produce reactive oxygen species generation [16] and intracellular calcium release [17]. Another noteworthy SNP in the bovine CXCR1 gene is SNP CXCR1-1768T>A, a transversion at position -1768 in the 5' upstream region of the bovine CXCR1 coding region [9].…”
mentioning
confidence: 93%